The correlation between school principal’s leadership and teacher’s productivity during Covid-19 pandemic - Putri, Febycia Mellania; Aisiyah, Laily Nur; Dienda Saputri, Senny Weyara; Rahman, Muhammad Habibu (Universitas Islam Negeri Raden Intan Lampung, 2022)
Teachers' productivity can't be separated from how the school principal's leadership acts in leading institutions. The lack of communication between the principal and the teachers in implementing emergency learning during the pandemic becomes the background of the study. This article aims to determine the correlation between the school principal's leadership and teachers' productivity during the COVID-19 pandemic. Ten teachers became the respondents of the study. The type of research is correlational research using rank-order formula. The method used in this study was quantitative data analysis. The result showed a good relationship between the school principal's leadership and teachers' productivity. The manual calculation showed that rcount was 0.745, higher than rtable (0.576). In percentage, the value obtained was 55.5%, and 44.5% of the value was affected by other factors. The criterion used was n=10 with rtable = 0.576 at a 95% significant level. The study found that the principal's control was very influential in maintaining the quality of education during a pandemic.